KENABIAN SEBAGAI TINDAKAN POLITIK - Asri, Syamsul (JPP (Jurnal Politik Profetik), 2017)
Prophethood (nubuwwah) is an implementation of the authority of divine lordship (to order and to protect) in a so-called divine city in which justice (‘adalah) as the fundamental objective of divine laws and politics may be rigidly enforced within the milieu of socio-politics. The purpose of this prophetic political engagement is to restore the ritual formal principles (i’tibari) of the sharia to its realistic fundamental principles (takwini) so that the Truth (al--Haq) may be flawlessly observed to its utmost level of possibilities.